Distribution Analysis of Glamping Tourism Support Facilities against Disaster-prone Areas in Kintamani District - Putu Wibby Prasetya (Tourism Department, State Polytechnic of Banyuwangi, 2025)
Kintamani District has amazing tourism potential, such as Caldera Batur, Lake Batur, Gunung Batur, Bali Aga Trunyan Village, and many more that makes Kintamani District one of the reasons why local and foreign tourists are interested. However, the rapid development of tourism that occurred resulted in many tourist support facilities, such as Glamping (Glamour Camping), which began to spread throughout the Kintamani sub-district. This is also of particular concern, as many glamping that are built is in the disaster-prone zone. This can harm tourists, especially tourists staying at the related glamping. The data used to analyze the spread is SHP (Shapefile) digitized the glamping spread location, which will be overlayed with disaster-prone SHP data. In the process, the Arcgis mapping application, 10.8 as well as Google Earthpro and SAS Planet support software was used. The results of this study are a map of glamping overlay analysis on disaster-prone zones in Kintamani District, which is an interpretation of which glamping locations are located in disaster-prone zones.